Solve for m mn=3m-2

Math
mn=3m-2
Subtract 3m from both sides of the equation.
mn-3m=-2
Factor m out of mn-3m.
Tap for more steps…
Factor m out of mn.
m(n)-3m=-2
Factor m out of -3m.
m(n)+m⋅-3=-2
Factor m out of m(n)+m⋅-3.
m(n-3)=-2
m(n-3)=-2
Divide each term by n-3 and simplify.
Tap for more steps…
Divide each term in m(n-3)=-2 by n-3.
m(n-3)n-3=-2n-3
Cancel the common factor of n-3.
Tap for more steps…
Cancel the common factor.
m(n-3)n-3=-2n-3
Divide m by 1.
m=-2n-3
m=-2n-3
Move the negative in front of the fraction.
m=-2n-3
m=-2n-3
Solve for m mn=3m-2

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top